Penerapan Algoritma Run Length Encoding Untuk Kompresi File Database *MySQL - Hutabarat, Esra Roma R (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
In the rapid development of technology, many information systems or applications already use databases for data storage. The database that is currently widely used for small and medium scale applications is MySQL. A common problem with database files is the amount of data or files stored in the database, which makes the database size large. In addition to the size of the database, there are also data sets that are responsible for reading records that take more time. Over time the database used increases, it will quickly fill disk space. One solution to this problem is to compress the data stored in the database. Compression algorithms, one of which is the Run Length Encoding (RLE) algorithm, and in this research, the algorithm used in MySQL Database File compression. The RLE (Run Length Encoding) algorithm is an encryption algorithm that encodes all data with the same value combined into one data value and the number of times that value appears.